Knowledge, attitude and behavior study on HIV awareness among continuous rotatory residential interns and postgraduates - Manoharan, K.; N., Sowmya; Kumar, N. Ashok; Manoharan, D. (International Journal of Research in Dermatology, 2021)
Background: Human immunodeficiency virus (HIV) that leads to Acquired immunodeficiency syndrome (AIDS) is transmitted mainly by sexual contact and exposure to infected blood. Healthcare workers (HCWs) such as Continuous rotatory residential interns (CRRIs) and postgraduates are at risk of acquiring HIV infection, primarily due to exposure to infected blood. The chances of infection depend on occupation, procedures performed, and use of preventive measures. The aim of the study was to access and compare knowledge, attitude and behavior about HIV awareness among CRRIs and Postgraduates. Methods: A cross sectional survey of 80 CRRIs and 80 postgraduates from Sree Balaji Medical College and Hospital was taken. A self-administered questionnaire was made and information regarding age, gender, knowledge about HIV, attitude and behavior towards HIV positive individual was gathered and compared between CRRIs and postgraduates. The data was compared and analyzed. Results: The results of the study revealed that postgraduates had better knowledge about routes of transmission of HIV compared to CRRIs. However, knowledge about preventive guidelines, vaccines and prophylaxis have to be improved by both postgraduates and CRRIs. Attitude towards HIV affected individual was positive. Behavior and practices followed to prevent HIV transmission have to be improved. Conclusions: HIV is an occupational hazard among HCWs. Appropriate knowledge about HIV is important. Attitude towards HIV infected individual plays an important role as it determines the care of the patient. Practicing standard guidelines while phlebotomy prevents the infection.